How E-Service Quality, Customer Rating, and Customer Engagement Affect Buying Decisions for Local Brand Flickabags - Selvia Rachmawati; Rita Ambarwati; Herlinda Maya Kumala Sari (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The current researcher discusses that the influence of e-service quality, customer ratings, and customer engagement in purchasing decisions affects the local retail production of Flickabags. And the researcher's question is whether e-service quality, customer ratings, and engagement influence e-commerce purchasing decisions. This researcher aims to identify marketing strategies to help deal with similar product competition from this local retail business, which focuses on service quality and information spread through its e-service quality as well as feedback from seller and buyer relationships. This research method uses a quantitative research model. The population obtained in this study is retail business e-commerce customers in the Sidoarjo district. The sampling technique in this study used a random sampling technique. The data collection technique in this study was a Google form questionnaire to the community in the Sidoarjo Regency area. The number of samples is determined based on calculations using the Cochran formula. Based on the output of SPSS, it is known that the significance value is 0.000 0.05, which simultaneously affects Y. And the F value calculated using table F is 130.108 F table 2.70 so that the results obtained are accepted, which means that each variable simultaneously affects Y. It is known that the R Square value is 0.799, so it can be concluded that the influence of each variable on the purchase decision is 79.9%. E-service quality, customer rating, and engagement impact in decision-making is 79.9%. This study shows a relationship between each variable and the purchasing decisions made by customers.